Hyperbaric oxygen effectively addresses the pathophysiology of long COVID: clinical review - Katz, Alan A.; Wainwright, Sandra; Kelly, Matthew P.; Albert, Pradeep; Byrne, Rosemary (Frontiers in Medicine, 2024)
Background The World Health Organization defines long COVID as “the continuation or development of new symptoms 3 months after the initial SARS-CoV-2 infection, with these symptoms lasting for at least 2 months with no other explanation.” Estimations of approximately 50 million individuals suffer from long COVID, reporting low health-related quality of life. Patients develop ongoing persistent symptoms that continue for more than 12 weeks that are not explained by another alternative diagnosis. To date, no current therapeutics are effective in treating the underlying pathophysiology of long COVID. Discussion A comprehensive literature search using PubMed and Google Scholar was conducted and all available articles from November 2021 to January 2024 containing keywords long covid and hyperbaric oxygen were reviewed. These published studies, including case series and randomized trials, demonstrate that utilizing Hyperbaric Oxygen Therapy (HBO) provided significant improvement in patients with long COVID. Conclusion A large cohort of patients suffer from long COVID or post-COVID-19 syndrome after recovery from their acute infection with no effective treatment options. HBO is a safe treatment and may provide benefit for this population and should continue to be researched for adjunctive treatment of long COVID.